The influence of adrenalin and pilocarpin oral gel on rat parodonte state - V. M. Batig; A. V. Borysenko; A. P Levitsky (Kazimierz Wielki University, 2017)
Aim: To determine the influence of adrenalin and pilocarpin upon periodontal tissues. Methods: The gels with adrenalin (0,36 mg/kg) and pilocarpin (2 mg/m) were applicated on oral mucosa everyday during 30 days. The activity of elastase, urease, lysozyme, catalase and contents of malonic dialdehide and hyaluronic acid were determined into gum. The activity of phosphates and contents of calcium and protein were determined into bone of parodonte. The degree of dysbiosis were calculated by ration activities of urease and lysozyme. The mineralisation index were calculated by ration activities of alkaline and acid phosphatases. The degree of bone mineralisation was determined by ration contents of alcium and protein. Results: The activity of elastase, the content of MDA and the degree of dysbiosis were lowered in gum after adrenalin application. The degree of dysbiosis was lowered in gum after application of pilocarpin. The mineralisation index of bone was lowered after adrenalin application. Conclusion: The adrenalin and pilocarpin make periodontoprotective effect.